Pengembangan Latihan Fisik untuk Kebugaran Atlet Dayung pada Masa Pandemi Covid-19 di Desa Buluhcina Kabupaten Kampar - Zahtamal, Zahtamal; Nazriati, Elda; Haslinda, Lilly (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The development of physical training for rowing athletes in Buluhcina village, Kampar Regency, still needs to be done, especially during the Covid-19 pandemic in 2020. The aim of this empowerment activity is to develop physical training for the fitness of rowing athletes, especially during the Covid-19 pandemic. The empowerment method used is education through question and answer lectures accompanied by simulations and demonstrations as well as optimizing the development of physical exercise. This empowerment activity has been carried out by always paying attention to health protocols during the Covid-19 pandemic. The results that have been obtained include increased knowledge of athletes, increased skills and motivation of athletes to continue to do physical exercise during Covid-19. This activity has also facilitated the development of facilities for athletes' physical fitness. The conclusion of this activity is the development of physical training for athlete fitness with this community service method has increased knowledge and optimized the fitness facilities for Rowing athletes